Sovereign bond prices, haircuts and maturity - Dirk Niepelt (University of Bern, Department of Economics, 2022)
We document that creditor losses ("haircuts") during sovereign debt restructurings vary across debt maturity. In our novel dataset on instrument-specific haircuts suffered by private creditors in 1999-2020 we find larger losses on short- than long-term debt, independently of the specific haircut measure we use. A standard asset pricing model rationalizes our findings under two assumptions, both of which are satisfied in the data: increasing short-run restructuring risk in the run-up to a restructuring, and high exit yields. We relate our findings to the policy debate on restructuring procedures.
Keywords: F34; F41; H63; 330; Sovereign Debt; Sovereign Default; Debt Restructuring; Bond Prices; Haircuts; Maturity; Restructuring Probability